Mechanisms of resistance to infection with Coccidioides immitis in mice. - Beaman, L V (1979)
Serum from vaccinated mice was ineffective in neutralizing the infectivity of arthrospores of Coccidioides immitis for recipient mice. However, a T-cell-enriched lymphocyte population was effective in preventing a lethal infection. Spleen cells from immune mice were passaged through nylon wool columns resulting in a T-cell enriched, B-cell-depleted population as shown by the susceptibility of the cell population to anti-theta serum and the inability of the cells to transfer adoptively an immune response to ovalbumin. Whereas transfer of 5 x 10(7) unfractionated immune spleen cells was required to protect 100% of the recipients against a lethal infection with C. immitis, 7 x 10(6) T-cell-enriched immune spleen cells were sufficient for the same level of protection. Thus, transfer of resistance to infection was achieved with fewer cells after the removal of B cells from the transferred spleen cells. The results confirm that T cells are crucial in transferring resistance against infection with C. immitis in mice.